Numerical computation of infinite Bessel transforms with high frequency. Issue 10 (3rd October 2018) - Chen, Ruyun; Kuang, Xuesong; Li, Zhi
ABSTRACT: In this paper numerical evaluation of infinite Bessel transforms with high frequency is considered. We first derive an asymptotic formula by using the integration by parts. Next we use an interpolation formula to evaluate the infinite Bessel transforms by choosing the suitable basis and nodes. The corresponding error results are proved, and numerical examples are shown to illustrate the efficiency and accuracy of the presented formulae.